Koreografi Tari Rancak Sumatera Di Sanggar Silodang Production Kota Padang - Fitri Latifah; Herlinda Mansyur (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to explain the choreography of Sumatran Rancak Dance at Sanggar Silodang Production Kota Padang. The type of research used is qualitative research with descriptive methods of analysis. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature study, observation, interviews, and documentation. The steps of analyzing data are data collection, data reduction, data presentation and data verification. The results showed that the choreography process carried out by choreographers has stages such as ideas / themes, exploration, improvisation, and composition. So from the process carried out by the choreographer produces the following aspects of form: motion, space design, time design, power design, upper design, dramatic design, floor design, group composition, equipment, and music. Sumatran Rancak dance has several types of movements consisting of movement developments from the regions of Aceh, Medan, Riau, and West Sumatra which are worked on by choreographers with the concept of entertainment. The costumes used have been created and modified using bludru brackets, metered songket, shoulder tokah, shoulder scarves, belts, and complete accessories for female dancers. As for male dancers, they wear satin, galembong, batik deta, and silodang cloth. Sumatran Rancak dance uses the plate property at the end of this dance with a plate size of 5.